Terapi nonfarmakologi rebusan daun sirih merah terhadap keputihan pada wanita - Wulandari, Tri (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2024)
IntroductionThe use of red betel leaf decoction among women of reproductive age experiencing symptoms of vaginal discharge has shown a significant decrease in symptoms. This is due to the presence of eugenol in red betel leaves, which has antifungal and analgesic properties, and tannins that help reduce vaginal secretions. This study aimed to determine the effectiveness of red betel leaf decoction in treating vaginal discharge in women living in Mekar Jaya Village, Tirta Harja Health Center, Muara Sugihan District, Banyuasin Regency.MethodThis research employed a quasi-experimental design with intervention and control groups. The independent variable in this study was red betel leaf decoction, while the dependent variable was the alleviation of vaginal discharge. The total number of respondents was 80, and total sampling was used to determine the sample size.ResultsThe statistical test showed that the Asymp. Sig (2-tailed) value was 0.00. Since 0.00 < 0.05, the hypothesis is accepted, indicating a significant difference between the intervention and control groups in terms of the healing of vaginal discharge. This implies that red betel leaf decoction is effective in treating vaginal discharge in women.Conclusion and RecommendationThe findings of this study are expected to serve as a reference for women experiencing vaginal discharge, suggesting that red betel leaf decoction can be considered a non-pharmacological treatment option.